Techniques and algorithms for computer aided diagnosis of pigmented skin lesions—A review. (January 2018) - Pathan, Sameena; Prabhu, K. Gopalakrishna; Siddalingaswamy, P.C.
Abstract: Computerized image analysis methods for dermoscopy are primarily of great interest and benefit, as it provides significant information about the lesion, which can be of pertinence for the clinicians and a stand-alone warning implement. Computer-based diagnostic systems require dedicated image processing algorithms to provide mathematical descriptions of the suspected regions, such systems hold a great potential in oncology. In this paper, we have performed a review of the state of art techniques used in computer-aided diagnostic systems, by giving the domain aspects of melanoma followed by the prominent techniques used in each of the steps. The steps include dermoscopic image pre-processing, segmentation, extraction and selection of peculiar features, and relegation of skin lesions. The paper also presents cognizance to judge the consequentiality of every methodology utilized in the literature, in addition to the corresponding results obtained in this perspective. The inadequacies and the future research directions are accentuated.